Inhibitory effects of omega-3 fatty acids on early brain injury after subarachnoid hemorrhage in rats: Possible involvement of G protein-coupled receptor 120/β-arrestin2/TGF-β activated kinase-1 binding protein-1 signaling pathway. (June 2016) - Yin, Jia; Li, Haiying; Meng, Chengjie; Chen, Dongdong; Chen, Zhouqing; Wang, Yibin; Wang, Zhong; Chen, Gang
Highlights: Omega-3 fatty acids inhibit post-SAH EBI via GPR 120/β-arrestin2/TAB1. Fish omega-3 fatty acids as part of a daily diet may reduce post-SAH EBI. GPR120 may serve as a new target for prevention and treatment of post-SAH EBI. Abstract: Omega-3 fatty acids have been reported to improve neuron functions during aging and in patients affected by mild cognitive impairment, and mediate potent anti-inflammatory via G protein-coupled receptor 120 (GPR120) signal pathway. Neuron dysfunction and inflammatory response also contributed to the progression of subarachnoid hemorrhage (SAH)-induced early brain injury (EBI). This study was to examine the effects of omega-3 fatty acids on SAH-induced EBI. Two weeks before SAH, 30% Omega-3 fatty acids was administered by oral gavage at 1 g/kg body weight once every 24 h. Specific siRNA for GPR120 was exploited. Terminal deoxynucleotidyl transferase dUTP nick end labeling, fluoro-Jade B staining, and neurobehavioral scores and brain water content test showed that omega-3 fatty acids effectively suppressed SAH-induced brain cell apoptosis and neuronal degradation, behavioral impairment, and brain edema. Western blot, immunoprecipitation, and electrophoretic mobility shift assays results showed that omega-3 fatty acids effectively suppressed SAH-induced elevation of inflammatory factors, including cyclooxygenase-2, monocyte chemoattractant protein-1, and inducible nitric oxide synthase. In addition, omega-3 fatty acids could inhibit phosphorylation of transforming growth factor β activated kinase-1 (TAK1), MEK4, c-Jun N-terminal kinase, and IkappaB kinase as well as activation of nuclear factor kappa B through regulating GPR120/β-arrestin2/TAK1 binding protein-1 pathway. Furthermore, siRNA-induced GPR120 silencing blocked the protective effects of omega-3 fatty acids. Here, we show that stimulation of GPR120 with omega-3 fatty acids pretreatment causes anti-apoptosis and anti-inflammatory effects via β-arrestin2/TAK1 binding protein-1/TAK1 pathway in the brains of SAH rats. Fish omega-3 fatty acids as part of a daily diet may reduce EBI in an experimental rat model of SAH.